Characteristics of Pineapple Waste as Liquid Organic Fertilizer and Its Effect on Ultisol Soil Fertility - Sutikarini Sutikarini; Agusalim Masulili; Rini Suryani; Setiawan Setiawan; Mulyadi Mulyadi (International Journal of Multi Discipline Science, 2023)
The Purpose to increase soil fertility can be carried out through the provision of liquid organic fertilizers by utilizing agricultural waste including pineapple waste. The research aims to determine the potential and chemical characteristics of pineapple peel waste and to determine the effect of liquid organic fertilizer dosage on increasing soil fertility of Ultisols. The research was conducted at the Faculty of Agriculture, Panca Bhakti University, Jl. Komyos Sudarso Pontianak had been held from June 2022-August 2022. The research used a completely randomized design (CRD), with dosage treatment of liquid organic fertilizer from pineapple plant waste P0 = 0 ml/l water, P1 = 15 ml/l water, P2 = 20 ml/l water, P3 = 25 ml/l water, P4 = 30 ml/l water, P5 = 35 ml/l water, P6 = 40 ml/l water, P7 = 45 ml/l water, P8 = 50 ml/l water. Data were analyzed using ANOVA, which showed a significant difference followed by an Honest Significant Difference (HSD) Test at the 5% level. Treatment of the dose of liquid organic fertilizer from pineapple waste can increase the fertility of ultisol, especially in soil pH, % C organic, % N of total soil, C/N ratio, and P and K content in Ultisol soil. Treatment of the dosage of liquid organic fertilizer for pineapple plant waste of 50 ml/l was the treatment that gave the best results on the parameters of soil pH, % C organic, % N of total soil, C/N ratio, the content of P and K elements in the soil.